Quotes and Images From The Diary of Samuel Pepys - Pepys, Samuel, 1633-1703; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2004)
"Quotes and Images From The Diary of Samuel Pepys" by Samuel Pepys is a collection of selected excerpts from the famous diary written in the 17th century. This historical account captures the daily life, circumstances, and observations of Pepys during a time of significant change in England, including events like the Great Plague and the Great Fire of London. The reflections offer insight into the social, political, and personal aspects of the era, making it an invaluable primary source for understanding life in the 1660s. The content of this book encompasses a variety of thoughts, reflections, and anecdotes shared by Pepys, revealing his experiences as a public servant and private individual. It includes his musings on love, politics, religion, and society, often presented with humor and candor. For instance, Pepys shares his encounters with significant historical events and figures, along with personal relationships and domestic life. The diary's vivid details and rich language paint a compelling portrait of daily life, providing readers a unique window into the human experience during a tumultuous period of history. (This is an automatically generated summary.)
Release date is 2004-09-03
Produced by David Widger
Keywords: Quotations